Tendencje w preferencjach i zachowaniach konsumentów na rynku dóbr FMCG - Idzik, Anna; Idzik, Marcin (Tendency in Consumer's Preference and Behavior on the FMCG Market, 2006)
The article presents a decision making process of the consumers related to FMCG (including food) purchases. The research shows that changes in Polish economy and globalization trends have an influence on consumer's preference and behavior. Among others graving time value for consumers, factors affecting a choice of a shop and consumer's favourite means of promotion are shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 312-320